REEVALUATING TEACHING STRATEGIES IN MATHEMATICS AND STATISTICS !N SECONDARY SCHOOLS - Mohd Sahar Sauian (Proceedings of ICMSA, 2005)
Numerous studies had shown that rural students are lagged behind inmathematical subjects compared to their urban counterparts,particularly in developing countries. This argument is normallycharacterized and expounded by exposing the negative factors such asstudents' attitude, cultural background, poor environment andfacilities, command of language, lack of graduate teachers as well aspoor mode of teaching methodologies. It has also been known thatthe single factor of "attitudinal problem" has chain-effects in their poorperformance in schools.This paper attempts to highlight some of the ways to arouse students'interest in leaming Mathematics and Statistics. Various teachingmethodologies suitable for rural students are discussed. Furthermore,the application of "contextual-based" teaching approach rather than the"content-based' teaching approach is found to be more beneficial forrural students in the teaching of mathematical subjects.Keywords: attitudinal problems, arxiety cycle, good mathematicslessorl contextual based teaching, content-based teachingexamination-oriented teaching, proactive modeling group tessellation.